A contabilidade das OSCIPS sediadas na grande São Paulo frente à adoção da resolução CFC Nº 1.409/2012 - Souza, Milton José de (2013)
Accounting has several essential purposes, among them social and financial, both for profit organizations and for nonprofit organizations. It seeks: to study, understand, record, analyze and evaluate facts that affect the assets of the organization. Accounting is based on its analysis of the facts and records related to the composition, movement and changes in equity of the entity, with the purpose of providing information to managers for the administrative and operational action, aimed at continuing entity. The present study aims at analyzing the use of accounting in nonprofit organizations qualified as OSCIP, the Greater São Paulo against CFC Resolution 1.409/2012. Knowing that these entities move more than 140 billion Reais per year, the society requires clarity of information provided and the entities seize these opportunities and fundraising opportunities for development of terms of partnerships, accounting information must be organized and ability to transmit necessary information to undestanding the funds raised and used. According to the Brazilian Association of Pickups Resources (ABCR) is nowadays a high degree of competition among entities for fundraising, especially after the international crisis that affected the world economy after 2008 and to enter this competitive market, it is fundamental to be aware for all variables that affect outcome in terms of the business of each of these organizations. Reviewing the literature, the study observes aspects of third sector organizations and their characteristics, the classification of these entities, their processes/accounting practices, as they are performed and presented the benefits of accounts and internal practices which are adopted by these organizations. The methodology used is a descriptive study, segmented into: data collection with questionnaire and field research in nonprofit organizations registered with the Ministry of Justice and have their registration for at least three years at CNES. The study results show how to use Accounting for nonprofit organizations qualified as OSCIP, the Greater São Paulo, showing that the entire sample surveyed these entities produce and distribute the balance sheet and other financial requirements such as the extinct DMPL, DOAR and current DRE, DFC and DVA beyond the current and still underexplored Social Balance. The disclosure of cost management is very low as only 45 % have the record of the costs of the services or products offered, thus demonstrating underutilization of accounting for managerial purposes. It was evident that there is a relationship between the positions/roles of VIII respondents and accounting practices of organizations surveyed, because it was found that the greater the responsibility of the respondent, the greater the return answers within that adopted the new standard, in addition to showing Accounting for the use of more broadly as the use of data for decision making